Aspects of organic chemistry of fullerenes - Hirsch, Andreas (Journal of Physics and Chemistry of Solids, 1997)
Successive additions to [60]fullerene show a remarkable degree of regioselectivity. Two characteristic examples of additions, namely nucleophilic cyclopropanations of 6-6 double bonds as well as formations of 5-6 bridged open azafulleroids, have been systematically investigated by analytical, spectroscopic as well as by computational methods. Regioselective additions to activated positions within the carbon framework of fullerene derivatives are the key steps for both controlled ring opening of the fullerene core and the synthesis of heterofullerenes. © 1997 Elsevier Science Ltd.